2019
DOI: 10.1161/atvbaha.118.312144
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Inhibitor Dickkopf 1

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…DKK1 is recognized as an inhibitor of the canonical WNT/β-catenin signaling pathway. 6 , 20 , 21 Platelets are the main source of circulating DKK1, and an increase in DKK1 leads to the formation of leukocyte-platelet aggregates (LPA), which facilitates leukocyte infiltration. 22 In the lung, DKK1 promotes macrophage and neutrophil infiltration by inhibiting the WNT pathway, and the infiltration of inflammatory cells is alleviated after inhibition of DKK1.…”
Section: Discussionmentioning
confidence: 99%
“…DKK1 is recognized as an inhibitor of the canonical WNT/β-catenin signaling pathway. 6 , 20 , 21 Platelets are the main source of circulating DKK1, and an increase in DKK1 leads to the formation of leukocyte-platelet aggregates (LPA), which facilitates leukocyte infiltration. 22 In the lung, DKK1 promotes macrophage and neutrophil infiltration by inhibiting the WNT pathway, and the infiltration of inflammatory cells is alleviated after inhibition of DKK1.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling pathway activation also contributed to functional recovery and increased neuroprotective processes and neurogenesis after cerebral ischemia [36]. As an antagonist of the Wnt pathway, Dkk1 prevents Wnt activation by binding to the Wnt receptor, leading to the activation of the Wnt/β-catenin signaling pathway [37]. Recent studies showed that Dkk1 is potentially induced in the hippocampal CA1 area after global cerebral ischemia, and administration of Dkk1 antisense oligonucleotides protects the CA1 region against cerebral ischemia-induced neuronal death [38].…”
Section: Discussionmentioning
confidence: 99%
“…The role of the DKK protein and secreted frizzled-related protein (sFRP) family in bone development, atherosclerosis and VC has been discussed in detail recently [76][77][78]. For this reason, we will further address the relationship between WNT inhibitors and VC in the following chapter.…”
Section: The Role Of Wnt Inhibitorsmentioning
confidence: 99%